PSYCHOLOGICAL STUDY: CHARACTERS IN THE PLAY MALAM JAHANAM BY MOTINGGO BOESJE - Naila Riski Ahsani; Ulfah Fauziah; Shifa Harun Salsabilah; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research was conducted to explore the psychology of the characters in the manuscript Malam Jahanam by Motinggo Boesje by studying through a literary psychology approach. This research explores two discussions, namely the character’s personality structure and the character’s conflict defense mechanism. These two studies are used to explore the psychology of the characters as a whole. This research uses a qualitative approach and qualitative descriptive method. The subject of this research is the play Malam Jahanam by Motinggo Boesje. The data collection technique used is the read-note technique. The results of this research discussion are two, namely A) The character’s personality structure is divided into three structures, namely Id, Ego, and Superego. B) The character’s conflict defense mechanism is divided into five, namely repression, sublimation, rationalization, formation reaction and aggression and apathy.